The Euclidean distribution of fast radio bursts. Issue 1 (10th June 2016) - Oppermann, Niels; Connor, Liam D.; Pen, Ue-Li
Abstract: We investigate whether current data on the distribution of observed flux densities of fast radio bursts (FRBs) are consistent with a constant source density in Euclidean space. We use the number of FRBs detected in two surveys with different characteristics along with the observed signal-to-noise ratios of the detected FRBs in a formalism similar to a V / V max -test to constrain the distribution of flux densities. We find consistency between the data and a Euclidean distribution. Any extension of this model is therefore not data-driven and needs to be motivated separately. As a byproduct we also obtain new improved limits for the FRB rate at 1.4 GHz, which had not been constrained in this way before.